NILAI TAIS DALAM TRADISI KEMATIAN MASYARAKAT SUKU KEMAK DI KABUPATEN BELU - AUGUSTA DE JESUS MAGALHAES (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
This study aims to determine the value contained in Tais in the tradition of death of the Kemak tribe community in Belu Regency. The type of research used is descriptive qualitative research. The results showed that the Tais by the Kemak tribe community is believed to contain a very high philosophical value and function in the death of the Kemak Tribe community in Kabuna village. Tais apart from being clothing in welcoming dances and traditional ceremonies, as a delivery item in a marriage ceremony which is a symbol of strengthening the relationship between the two parties, far from that tais is an expression of feeling sorry for, as a symbol of respect for deceased relatives, and also become a means of connecting between individuals and ancestors. Therefore, the kemak tribe community, needs to be given an understanding in maintaining the existing Tais values, and good cooperation between the community, traditional elders or community leaders and the local government.